2010
DOI: 10.1165/rcmb.2009-0002oc
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylinositol-3-Kinase/Akt Regulates Bleomycin-Induced Fibroblast Proliferation and Collagen Production

Abstract: Abnormal repair and dysregulated angiogenesis have been implicated in the pathogenesis of pulmonary fibrosis, but the underlying mechanisms of regulation are not well understood. The present study investigated the role of phosphatidylinositol-3-kinase (PI3K)/ Akt in fibrogenesis of human lung fibroblasts and its regulation by reactive oxygen species (ROS). Exposure of lung fibroblasts to bleomycin, a known inducer of fibrosis, resulted in rapid activation of PI3K/Akt and a parallel increase in fibroblast proli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
96
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(117 citation statements)
references
References 52 publications
(66 reference statements)
9
96
0
Order By: Relevance
“…Recently, the PI3K/Akt pathway was reported to regulate proliferation and collagen production in lung fibroblasts exposed to bleomycin (27). On the basis of the findings that bleomycin induced VEGF release from lung fibroblasts, and that VEGF caused proliferation and collagen production, this report suggested that VEGF was in part responsible for fibroblast activation.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Recently, the PI3K/Akt pathway was reported to regulate proliferation and collagen production in lung fibroblasts exposed to bleomycin (27). On the basis of the findings that bleomycin induced VEGF release from lung fibroblasts, and that VEGF caused proliferation and collagen production, this report suggested that VEGF was in part responsible for fibroblast activation.…”
Section: Discussionmentioning
confidence: 96%
“…In human lung fibroblasts, Col1A1 mRNA is stabilized in a PI3K-dependent manner (40), and bleomycin-induced collagen production is regulated by PI3K/Akt (27). LY294002 was found to completely abolish collagen production and to induce a significant decrease in secretion of laminin ␤2 and fibronectin from keloid fibroblasts (26).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is characterized by prominent fibroblast proliferation and amplified deposition of extracellular matrix (ECM) (Lu et al, 2010). The pathogenesis of pulmonary fibrosis is not clearly defined, with the evidence of abnormal parenchymal repair, aberrant vascular remodeling and neoangiogenesis, which are seen in both animal models and patient samples (Nobel and Norman, 2003;Steurer et al, 2007).…”
Section: Introductionmentioning
confidence: 99%